EFT (Emotional Freedom Technique) As An Alternative Therapy To Reduce Anxiety Disorders and Depression in People Who Are Positive Covid-19 - Tambunan, Marcelina Boru; Suwarni, Linda; Setiawati, Linda; Mardjan, Mardjan (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2022)
The increasing number of deaths from Covid-19 is in line with anxiety disorders and depression in people who are positive for Covid-19. The emotional Freedom Technique (EFT) is known as an effective therapy to reduce mental health disorders in certain patients but has never been applied to people who are confirmed positive for Covid-19. This study aims to analyze the effectiveness of EFT as an alternative therapy in reducing anxiety and depression in people who are positive for Covid-19. This research design uses a quasi-experimental approach with a one-group pretest and posttest approach. A total of 22 people were isolated in the Health Training Unit (UPELKES) provided by the Pontianak Government in June 2021. The data analysis technique used paired t-test (95% CI). There was a significant decrease in anxiety (t value = 6,738) and depression scores (t value = 2,585) after EFT therapy was given (p-value < 0.05). Thus, EFT can be an alternative therapy in overcoming anxiety and depression disorders in people who are confirmed positive for Covid-19.Meningkatnya angka kematian akibat Covid-19 seiring dengan gangguan kecemasan dan depresi pada orang yang positif Covid-19. Emotional Freedom Technique (EFT) dikenal sebagai terapi yang efektif menurunkan gangguan kesehatan mental pada pasien tertentu, namun belum pernah diaplikasikan pada orang yang terkonfirmasi positif Covid-19. Penelitian ini bertujuan untuk menganalisis efektivitas EFT sebagai terapi alternatif dalam menurunkan gangguan kecemasan dan depresi pada orang yang positif Covid-19. Desain penelitian ini menggunakan quasy experimental dengan pendekatan one group pretest and posttest. Sebanyak 22 orang yang diisolasi di Unit Pelatihan Kesehatan (UPELKES) yang disediakan Pemerintah Pontianak pada bulan Juni 2021. Teknik analisis data menggunakan paired t test (95% CI). Terdapat penurunan skor gangguan kecemasan (nilai t = 6,738) dan depresi (nilai t = 2,585) yang signifikan setelah diberikan terapi EFT (p value < 0,05). Dengan demikian, EFT dapat menjadi terapi alternatif dalam mengatasi gangguan kecemasan dan depresi pada orang yang terkonfirmasi positif Covid-19.